Pain Assessment and Management in Pediatric Intensive Care Units Around the World, an International, Multicenter Study - Grunauer, Michelle; Mikesell, Caley; Bustamante, Gabriela; Cobo, Gissela; Sánchez, Sebastián; Román, Ana María; Icaza-Freire, Andrea P.; Gavilanes, Antonio W. D.; Wang, Nancy Ewen, The PICU-MIC Research Group; González, Jorge López; López-Herce, Jesús; et al. (Frontiers in Pediatrics, 2021)
The adequate assessment and management of pain remains a challenging task in the Pediatric Intensive Care Unit (PICU). Our goal is to describe how pain is assessed and managed in PICUs around the world and to examine how human and material resources impact achievement of this goal. An international multicenter cross-sectional observational study was designed with the participation of 34 PICUs located in urban, suburban, and rural areas of 18 countries. We evaluated how PICUs around the world assessed and managed pain according to the Initiative for Pediatric Palliative Care recommendations, and how human and material resources impacted achievement of this goal. Data was collected for this study from 2016 to 2018 using questionnaires completed by medical doctors and nurses. In this paper, we focus on the indicators related to how pain is managed and assessed. The average achievement of the goal of pain relief across all centers was 72·2% (SD: 21·1). We found a statistically significant trend of more effective pain management scores, routine assessment, proper documentation, and involvement of pain management experts by increasing country income. While there are efforts being made worldwide to improve the knowledge in pain assessment and management, there is a lack of resources to do so appropriately in low-middle-income countries. There is a mismatch between the existing guidelines and policies, which are mainly designed in high income countries, and the resources available in lower resourced environments.